HUBUNGAN AKTIVITAS KELUARGA DENGAN TINGKAT KEMANDIRIAN DALAM MERAWAT PENDERITA DM TIPE 2 - Dahliyani ' '; Arneli wati '; Wasisto utomo ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract Diseasetype 2 diabetesifnotaddressedcanlead tocomplicationsrequiredroleinthe activity ofan activefamilywith adegree of independenceindependent familiesin caring forpatients withtype 2 DM. The purpose of this research is to identify the relationship between family activity and   level of independence in treating the patient with type 2 DM. Research design used in this research was an analytical survey by using cross sectional approach. This research was conducted at the health center Bumi Ayu and health center Dumai City. Number of samples 59 persons of total sample which were taken by using sampling method was in accordance with non probability sampling. It was an accidental sampling with due regard to inclusion criteria. The measuring instrument was a questionnaire consist of 25 questions which has tested validity and reliability. Data analysis methods used were univariate and bivariate with Chi-Square test.The experimental result showed that there is a relationship between family activity and level of independence in treating the patient with type 2 DM, with the value of p-value=0,002. According to the result, the family is expected to further improve family activity that affects the level of independence in caring for patients with type 2 DM.. Keywords        : Family activity, level of independence, type 2 DM.